Horizontally and vertically aligned growth of strained MoS2 layers with dissimilar wetting and catalytic behaviors. Issue 34 (9th August 2017) - Kumar, Pawan; Viswanath, B.
Abstract : We report the chemical vapor deposition (CVD) based growth of aligned MoS2 two-dimensional (2D) nanostructures and their wetting and catalytic behaviors. Abstract : We report the chemical vapor deposition (CVD) based growth of aligned MoS2 two-dimensional (2D) nanostructures and their wetting and catalytic behaviors. Controlling the alignment of atomically thin MoS2 layers provides an excellent platform to tune the contact angle from ∼70° to ∼106°, leading to a transition from hydrophilic to hydrophobic surfaces. We also tested the catalytic performance of surface engineered MoS2 nanostructures and found that vertically aligned MoS2 with a hydrophobic surface shows a higher current density at lower potential for the hydrogen evolution reaction (HER). The observed unusual behavior of the hydrophobic surface showing better HER performance is further explained by the high electrochemical surface area of vertically aligned MoS2 nanostructures. Horizontal and vertical growth of MoS2 is achieved by tuning the supersaturation by varying the S : MoO3 ratio and the distance between them. Mechanistic understanding of MoS2 growth and alignment has been developed with the aid of detailed atomic force and electron microscopy observations. High resolution transmission electron microscopy (HRTEM) and Raman spectroscopy investigations of strained atomically thin layers in vertically aligned MoS2 revealed the role of strain variation in stabilizing the self-standing vertical alignment of 2D nanostructures. The presented results of tuning the wettability of semiconducting MoS2 by controlling the aligned growth of 2D materials and their electrochemical performance are relevant for smart surface, water splitting and energy storage applications.